Transformation der Medien - Medien der Transformation Verhandlungen des Netzwerks Kritische Kommunikationswissenschaft - Borchers, Nils S.; Güney, Selma; Krüger, Uwe; Schamberger, Kerem (Westend Verlag, 2021)
The media landscape is undergoing an epochal upheaval due to digitalisation and globalisation. But what opportunities and what dangers does the internet hold for democratic discourse? What role do corporations and platform capitalists play in media change? Is everything always getting worse, or can journalism, social media and public relations also contribute to making the world a better place and bringing about a socio-ecological change towards sustainability? And what can we learn from previous media upheavals like the one in East Germany after the fall of the Berlin Wall? These and other questions are examined by 27 authors from a variety of perspectives.